2014
DOI: 10.1016/j.chembiol.2014.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Acyl Carrier Protein Interactions of an Acyl-CoA Promiscuous trans-Acyltransferase

Abstract: SUMMARY Protein interactions between acyl carrier proteins (ACP’s) and trans-acting acyltransferase domains (trans-AT’s) are critical for regioselective extender unit installation by many polyketide synthases. Yet, little is known regarding the specificity of these interactions, particularly for trans-AT’s with unusual extender unit specificities. Currently, the best-studied trans-AT with non-malonyl specificity is KirCII from kirromycin biosynthesis. Here, we developed a new assay to probe ACP interactions ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Similarly, several trans -AT KSs that catalyze polyketide chain elongation do not contain a flanking subdomain, yet the corresponding ACPs from these modules must interact with a trans -AT (e.g., ChiKS16, LnmKS3, MlnKS8, and DifKS10). Studies have shown that trans -ATs are capable of charging ACP domains in the absence of a KS or flanking subdomain and that a trans -AT from the kirromycin PKS (KirCII) is quite specific for its cognate ACP 14,26,2830 . This degree of trans -AT specificity for an ACP is surprising if the flanking subdomain or KS body is selective for docking with a particular trans -AT.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several trans -AT KSs that catalyze polyketide chain elongation do not contain a flanking subdomain, yet the corresponding ACPs from these modules must interact with a trans -AT (e.g., ChiKS16, LnmKS3, MlnKS8, and DifKS10). Studies have shown that trans -ATs are capable of charging ACP domains in the absence of a KS or flanking subdomain and that a trans -AT from the kirromycin PKS (KirCII) is quite specific for its cognate ACP 14,26,2830 . This degree of trans -AT specificity for an ACP is surprising if the flanking subdomain or KS body is selective for docking with a particular trans -AT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ATs are key determinants of building block specificity in polyketide biosynthesis and attractive targets to change the substrate specificity to obtain biologically active unnatural polyketide products (5). However, the substitution of an AT domain by a homologous AT domain possessing different substrate specificity resulted in reduced or abolished production of polyketide analogs in many cases, probably because of disruption of proper protein-protein interactions or the inability of downstream modules to process polyketide analogs (5, 6).The importance of protein-protein interaction between AT and ACP during the acyltransfer reaction was proposed in previous studies (7,8). Wong et al described that AT recognizes its cognate ACP from other ACPs through protein-protein interactions (7).…”
mentioning
confidence: 99%
“…The importance of protein-protein interaction between AT and ACP during the acyltransfer reaction was proposed in previous studies (7,8). Wong et al described that AT recognizes its cognate ACP from other ACPs through protein-protein interactions (7).…”
mentioning
confidence: 99%
“…Kirromycin biosynthesis was the first described example of an alliance between a cis-ATP-type PKS with trans-AT-type PKS in a single pathway [58]. Its biosynthesis, as well as its application for synthetic biological approaches has been reported in recent years [25,27,40,61].…”
Section: Kirromycinmentioning
confidence: 99%